THE ROLE OF INTERNAL SUPERVISION IN REPOSITIONING SECONDARY SCHOOL ADMINISTRATION IN ENUGU STATE, NIGERIA - Amaka Onu, Eucharia; Omeke, Faith; Ozioko, Agatha; Edikpa, Edith (International Journal of Psychosocial Rehabilitation, 2024)
The study investigated the role of internal supervision in repositioning secondary schooladministration in Enugu State, Nigeria. A descriptive survey design was adopted for the study.The population of the study consists of 92 teachers from the selected 25 secondary schools inNsukka education zone, Enugu state. Purposive sampling technique was adapted to the study. Asample size of 78 teachers was used because most of the teachers were on leave. A wellstructured Questionnaire titled the role of internal supervision in repositioning secondary schooladministration in Enugu state (QRISRSSA) containing 17 items were the instrument for datacollection. The instrument was validated by three experts from the University of Nigeria, Nsukka.The validated instrument was trial tested, using 20 respondents which comprised of 15 femaleteachers and 5 male teachers outside the study area. Cronbach alpha method was used todetermine the internal consistency of the instrument which gave overall reliability of 0.81. Meanand standard deviation were used in data analysis. The study revealed that the schooladministrators should endeavor to involve in thorough evaluation and monitoring of the schoolacademic performance of the students, supervision of instructional delivery of the teachers,teachers and the no-tutorial staffs should be motivated as when due, and provision of qualityinstructional materials for effective teaching and learning should be taken into consideration.Based on the findings, it was recommended among others that the school administrators in  sukka education zone should organize seminars, symposium, conferences and workshop inorder to sensitize the staff on the relevance of internal supervision in circular schools.